2018
DOI: 10.1002/pi.5719
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of POSS hybrid organogels using Menschutkin quaternization chemistry

Abstract: The present research describes a series of organic–inorganic hybrid gels based on polystyrene and polyhedral oligomeric silsesquioxanes (POSSs) prepared using free radical copolymerization and Menschutkin chemistry techniques. In the first step, poly(styrene‐co‐chloromethylstyrene) is readily achieved by thermally initiated radical copolymerization and the subsequently obtained copolymer reacts with diethanolamine functional POSS nanoparticles which are employed as the crosslinker. The resulting hybrid network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It was found that the inherent strength and rigidity of the inorganic POSS siliceous nucleus as well as the springiness of organic side substituents (R) can improve the overall performance of POSS/polymer nanohybrid matrices. In these nanohybrid materials, well‐dispersed POSS nanoparticles can enhance the morphological, mechanical, thermal, oxidative and biostability properties of hybrid polymers under critical situations …”
Section: Introductionmentioning
confidence: 99%
“…It was found that the inherent strength and rigidity of the inorganic POSS siliceous nucleus as well as the springiness of organic side substituents (R) can improve the overall performance of POSS/polymer nanohybrid matrices. In these nanohybrid materials, well‐dispersed POSS nanoparticles can enhance the morphological, mechanical, thermal, oxidative and biostability properties of hybrid polymers under critical situations …”
Section: Introductionmentioning
confidence: 99%
“…Hydrophobic network structures are made intermolecularly by chemical or physical crosslinking and these soft materials can absorb appropriate non‐aqueous solvents depending on their chemical structures. Despite the solvent absorption of polymer gels, crosslink structures can be responsive under special conditions such as change of electric field, solvent polarity, pH, and dose of light irradiation . Organogels show fascinating properties in drug delivery, dye, and heavy metal removal applications .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we designed polystyrene and amine functionalized polysilsesquioxane (POSS)‐based hybrid organogels via free‐radical polymerization and quaternization chemistry. Synthesized hybrid gels exhibited very good solvent uptake and good mechanical properties …”
Section: Introductionmentioning
confidence: 99%